Oxysterols in cancer management: From therapy to biomarkers. (18th October 2020) - Kloudova‐Spalenkova, Alzbeta; Holy, Petr; Soucek, Pavel
Abstract : Oxysterols are oxidized derivatives of cholesterol, both endogenous and exogenous. They have been implicated in numerous pathologies, including cancer. In addition to their roles in carcinogenesis, proliferation, migration, apoptosis, and multiple signalling pathways, they have been shown to modulate cancer therapy. They are known to affect therapy of hormonally positive breast cancer through modulating oestrogen receptor activity. Oxysterols have also been shown in various in vitro models to influence efficacy of chemotherapeutics, such as doxorubicin, vincristine, cisplatin, 5‐fluorouracil, and others. Their effects on the immune system should also be considered in immunotherapy. Selective anti‐cancer cytotoxic properties of some oxysterols make them candidates for new therapeutic molecules. Finally, differences in oxysterol levels in blood of cancer patients in different stages or versus healthy controls, and in tumour versus non‐tumour tissues, show potential of oxysterols as biomarkers for cancer management and patient stratification for optimization of therapy. LINKED ARTICLES: This article is part of a themed issue on Oxysterols, Lifelong Health and Therapeutics. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.16/issuetoc